The incompatibility of Canadian rehabilitative sentencing goals and current penal practices: the necessity of critically adopting a Norwegian-inspired rehabilitative prison model - Strelnikova, E (2024)
Despite its emphasis on rehabilitation, the Canadian prison system remains overly punitive in practice, failing to successfully reintegrate offenders and reduce recidivism. Adopting a Norwegian-inspired rehabilitative prison model based on components of the penal system that have been proven to work already could better align the Canadian criminal justice system with its sentencing goals. Though limited by data availability, official reports and academic literature from Canada and Norway are used to critically analyze sentencing laws and correctional policies and how they contrast to quantitative and qualitative prison statistics. While both countries emphasize rehabilitation rhetorically, Canadian prisons are punitive, while Norwegian prisons achieve their rehabilitative aims. To improve prison conditions and offender outcomes, Canadian prisons should implement Norwegian sentencing principles, including the principle of normality and the importation model, focusing on promoting offenders’ community links and humane facilities. Critical considerations include implementation structure, managing dangerous offenders, and why Indigenous healing lodges, despite presenting similarities, cannot fill this reform need. Potential benefits include adhering to recent legislation, reducing reoffending, community engagement, and shorter sentences.